Wax Ester Analysis of Bats Suffering from White Nose Syndrome in Europe - Řezanka, Tomáš; Viden, Ivan; Nováková, Alena; Bandouchová, Hana; Sigler, Karel (Lipids, 2015)
The composition of wax esters (WE) in the fur of adult greater mouse-eared bats (Myotis myotis), either healthy or suffering from white nose syndrome (WNS) caused by the psychrophilic fungus Pseudogymnoascus destructans, was investigated by high-resolution mass spectrometry analysis in the positive ion mode. Profiling of lipid classes showed that WE are the most abundant lipid class, followed by cholesterol esters, and other lipid classes, e.g., triacylglycerols and phospholipids. WE abundance in non-polar lipids was gender-related, being higher in males than in females; in individuals suffering from WNS, both male and female, it was higher than in healthy counterparts. WE were dominated by species containing 18:1 fatty acids. Fatty alcohols were fully saturated, dominated by species containing 24, 25, or 26 carbon atoms. Two WE species, 18:1/18:0 and 18:1/20:0, were more abundant in healthy bats than in infected ones.
Keywords: Male; Fatty Alcohols; Chiroptera; Mycoses; sexuální faktory; mastné kyseliny; Europe; mykózy; mužské pohlaví; Mass Spectrometry; Fatty Acids; vlasy, chlupy; Nose; Evropa; lipidy; Animals; ženské pohlaví; nos; zvířata; Sex Factors; mastné alkoholy; Lipids; hmotnostní spektrometrie; Female; Hair